Chitosan Film with Citrus limonia Essential Oil: Physical and Morphological Properties and Antibacterial Activity - de Oliveira Filho, Josemar Gonçalves; de Deus, Isabella Pelosi Borges; Valadares, Anna Carolina Fernandes; Fernandes, Cassia Cristina; Estevam, Elisângela Barbosa Borges; Egea, Mariana Buranelo (Colloids and interfaces, 2020)
The development of active packaging for food preservation is attracting increased attention due to serious environmental problems caused by synthetic and conventional materials. In the present study, the physical, chemical, optical, microstructural, and antibacterial properties of chitosan films with Citrus limonia essential oil (CEO) were investigated. The incorporation >0.75% of CEO increased the thickness of the films. The incorporation >0.25% of CEO reduced the moisture content and the water vapor permeability of the chitosan films. The biodegradability of the films over ten days ranged from 55.46–62.65% and was not affected by the addition of CEO. All films showed good UV light barrier properties, and the incorporation of the CEO caused a decrease in the visible light transmission rate values. The addition of CEO changed the color of the bioactive films significantly, remain darker and yellowish. The bioactive films showed antibacterial activity against Staphylococcus aureus, but not against Escherichia coli. The films showed a heterogeneous microstructure with oil droplets retained in the continuous polysaccharide network. The results showed that chitosan films with CEO are promising as an active packaging material for food preservation.